Antecedents and effects of free riding in the franchisor–franchisee relationship - Kidwell, Roland E.; Nygaard, Arne; Silkoset, Ragnhild (Journal of Business Venturing, 2007)
This field study investigated contextual antecedents of free riding by franchisees on franchisor brand reputation and effects of free riding on performance in a multinational corporation's franchising network. Structural elements (increased formalization, decentralized decision-making), interactions between franchisor representatives and franchisee dealers, and market-related factors (external competition) were associated with lower levels of franchisee free riding. The findings also indicated that free riding has deleterious effects on franchisee performance. The results support theoretical arguments that both economic and social exchange perspectives are valuable in examining free riding and provide important practical guidance in designing and managing franchise systems.